Evaluation of vitamin D levels and body mass indexes of university employees - MAVİŞ, Murat Emrah; YILDIRIMMAVİŞ, Çiğdem; ARANCIOĞLU, İrem ÖZAY; YILMAZ, Hatice Kübra; ERGÜDEN, Berrak; HATEMİ, Hasan Hüsrev (Bangladesh Journal of Medical Science, 2020)
Objective: Vitamin D is known to have important effects on human health. The existence of a relationship between obesity and vitamin D levels, which have been shown to cause a number of health problems with various studies, is certain. In this study, the relationship between vitamin D levels and body mass indexes(BMI) of individuals was evaluated. The study is unique for being the only research on literature that carried out with university employees. Materials and methods: Blood samples, anthropometric measurement (BMI) was obtained from 87 volunteer working at Haliç University. The questionnaire form covering the basic questions applied by means of face-to-face method. Quantification of the analytes for 25-hydroxyvitamin-D was carried out using LC-MS/MS. The relationship between 25-hydroxyvitamin-D values and BMI was evaluated with Tukey HSD multiple comparison test. 95% confidence and 80% power sampling were applied to the predictions of a minimum0.50 connection coefficient between 2 quantitative variables.The necessity of 30 cases was determined by using the N = [(Zα+Zβ)/C]2 + 3formula.Considering the losses, the work will be carried out over 80 people. Results and Discussion: There’s significant difference between 25-hydroxyvitamin-D2 and 25-hydroxyvitamin-D3 and the BMI levels of the subjects(p:0.028<0.05-p:0.000<0.05). The average 25-hydroxyvitamin-D3 and 25-hydroxyvitamin-D2 levels of overweight participants were significantly higher than the mean levels of underweight participants’. No significant relationship was found between 25-hydroxyvitamin-D3 and 25-hydroxyvitamin-D2 levels and the time spent outdoors during summer and winter. Conclusion: To prevent vitamin D deficiency and insufficiency is to obtain some sensible sun exposure, ingest foods that contain vitamin D, and take supplement. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.229-236